The Effects of Complex Training on Functional Fitness Performance in Middle-aged and Elderly Adults (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
The Effects of Complex Training on Functional Fitness Performance in Middle-aged and Elderly Adults